2001
DOI: 10.1136/jech.55.4.246
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood level and individual level SES effects on child problem behaviour: a multilevel analysis

Abstract: Objective-This study examined whether neighbourhood level socioeconomic variables have an independent eVect on reported child behaviour problems over and above the eVect of individual level measures of socioeconomic status. 45).Conclusions-Living in a more deprived neighbourhood is associated with higher levels of child problem behaviour, irrespective of individual level socioeconomic status. The additional eVect of the neighbourhood may be attributable to contextual variables such as the level of social cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
108
2
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 18 publications
9
108
2
2
Order By: Relevance
“…Possibly, the variation in SES in these low SES inner-city areas is too small to detect associations between SES and the prevalence of psychiatric disorders. Another explanation may be that the influence of living in a deprived neighborhood outweighs the effect of the individual level of SES on the prevalence of psychiatric disorders (Kalff et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the variation in SES in these low SES inner-city areas is too small to detect associations between SES and the prevalence of psychiatric disorders. Another explanation may be that the influence of living in a deprived neighborhood outweighs the effect of the individual level of SES on the prevalence of psychiatric disorders (Kalff et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the hypothesis that neighborhood characteristics like median household income and level of violent crime may serve as proxy risk factors, which are only associated with depressive symptoms through their relation with family income. However, other studies have observed a significant effect of neighborhood deprivation on internalizing symptoms or behavior problems in younger age groups, even after adjusting for individual-level SES and other demographic characteristics (Caspi et al, 2000;Kalff et al, 2001;Xue et al, 2005), though few studies have evaluated the influence of neighborhood residence on the risk of depression among older children using objective measures of neighborhood characteristics. The Moving to Opportunity Study demonstrated that children whose families moved from high-to low-poverty neighborhoods experienced significant declines in anxious and depressive symptoms, compared to children in families who remained in impoverished neighborhoods, but only among boys (Leventhal & Brooks-Gunn, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, little evidence exists as to whether neighborhood characteristics like poverty and violent crime influence depressive symptoms in children and adolescents independent of their association with family SES, as many studies of the relations between neighborhood characteristics and depressive symptoms have not included adjustment for family SES (e.g. Ozer & Weinstein, 2004) and few studies have looked explicitly at depressive symptoms, focusing instead on problem behaviors or developmental and academic outcomes (Brooks-Gunn et al, 1993;Kalff et al, 2001;Leventhal & Brooks-Gunn, 2000). We hypothesize that neighborhood characteristics are proxy risk factors (Kraemer et al, 2001) for family income, associated with depressive symptoms only through their relation with family income (Figure 1c).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-level parental occupation (Campbell, 1995;Kalff et al, 2001a), family size (Williams et al, 1990), race (Costello et al, 1996), family structure (Velez et al, 1989), low maternal age at delivery (Orlebeke et al, 1998), and maternal depression (Lavigne et al, 1998) are important family-related risk factors. Although the environment in which a child grows up is a potential risk factor for behavioral problems (Kalff et al, 2001b), little is known about its influence on DSM-based diagnoses (Hermanns and Leu, 1998). Data were collected during a longitudinal population study in the south of the Netherlands, titled the Study of Attention Disorders in Maastricht (SAM), that used a two-stage design (Kalff et al, 2001a;Kroes et al, 2001).…”
Section: A Longitudinal Community Study: Do Psychosocial Riskmentioning
confidence: 99%